Genome of elegance coral Catalaphyllia jardinei (Euphylliidae) - Yifei Yu; Wenyan Nong; Wai Lok So; Yichun Xie; Ho Yin Yip; Jasmine Haimovitz; Thomas Swale; David M. Baker; William G. Bendena; Ting Fung Chan; Apple P. Y. Chui; Kwok Fai Lau; et al. (Frontiers in Marine Science, 2022)
Coral reefs are under stress throughout the world. To better understand the molecular mechanisms underlying coral biology and their genomic evolution, here we sequenced the genome and transcriptomes of elegance coral Catalaphyllia jardinei (Euphylliidae). This monotypic genus stony coral is widespread but rare, being found across the Indo-West Pacific, from the northern Indian Ocean, Australia, Philippines, to the South China Sea. Due to its popularity among aquarium hobbyists, it is an overexploited species collected in large quantities from the wild for aquarium trade. The assembled genome is ~ 651.3 Mb in total length and of high physical contiguity with a scaffold N50 size of 28.9 Mb. The gene copy numbers of abiotic stress regulator (heat shock protein family genes) and neuropeptides (GLWamide, GRFamide, PRGamide and HIRamide) are similar to other sequenced anthozoans, and we have also identified the first set of sesquiterpenoid biosynthetic pathway genes in coral. Sequencing of small RNAs allows us to identify 35 microRNAs in C. jardinei and update the number of conserved microRNAs in cnidarians. This study established a foundation for further investigation into the roles of sesquiterpenoids and microRNAs in development of coral and understand their responses to climate change. Due to the easiness to culture C. jardinei in reef tanks and the established resources in this study, we propose this species be adopted as a new laboratory model in environmental and ecological experiments aiming to understand coral biology and responses to environmental stressors.